Adsorption studies of methylene blue onto activated saw dust: Kinetics, equilibrium, and thermodynamic studies - Banerjee S.; Chattopadhyaya M.C.; Srivastava V.; Sharma Y.C. (My University, 2025)
This study is devoted to the application of activated saw dust (ACSD) as adsorbent for the removal of "methylene blue (MB)" from the aqueous solutions. Raw saw dust was activated by a simple and low cost chemical method. After activation, adsorbent was characterized by scanning electron microscopy for its surface characteristics. Brunauer-Emmett-Teller surface area and average particle size were determined and found to be 74.23 m2/g and 700 μm, respectively. Removal efficiency of adsorbent for MB was demonstrated by batch adsorption experiments. pH study indicates that 9.5 pH is optimum for higher removal of MB. Temperature studies revealed exothermic nature of adsorption process. On studying kinetic models, it was observed that removal process is governed by pseudo-first-order kinetics. Intraparticle diffusion study revealed that it is not rate limiting step in removal process. Mass transfer coefficient was also determined. Value of ΔG° was found to be negative at all studied temperature which confirms the feasibility of process. Langmuir's adsorption isotherm was found to be suitable for this system. This study revealed that ACSD can be used as alternates of costly adsorbents for the removal of MB from effluents. © 2013 American Institute of Chemical Engineers.